A ressonância do ser: contribuição metodológica para a percepção de sentidos religiosos em canções de Noel Rosa, Lupicínio Rodrigues e Caetano Veloso - Souza, Antonio Passos de (2024)
This dissertation aims to contribute to the expansion of interpretative reach in the field of studies focused on the presence of religious senses in songs of Brazilian popular music. Therefore, it is structured in three moments: a) elaboration of an instrumental theoretical arc; b) undertaking a succession of methodological reflections about how to do; and c) demonstrative use of the theoretical-methodological framework in the hermeneutics of four songs: Feitio de Oração (Vadico and Noel Rosa, 1933), Felicidade (Lupicínio Rodrigues, 1947), Minha Mulher (Caetano Veloso, 1975) and Pulsar (Caetano Veloso and Augusto de Campos, 1984). The theoretical articulation proposed starts from the theology of culture (Tillich) – a consolidated reference in the thematic field – in dialogue with the phenomenology of religion (Eliade) and with some more conceptions identified as complementary contribution: coming from theories of the imaginary, philosophy and psychology. From the methodological point of view, some guidelines were found to be fundamental in the research context: the option for an approach to the organic unity of the song (lyrics and music), the relevance of hearing as a hermeneutic procedure and the openness to the intuitive as a cognitive way. In this way the dissertation suggests the configuration of a dissimilar contribution offered by the Sciences of Religion to the studies on Brazilian popular music: the recognition of the experience of mystery as a vital force in the songs. The religious sense, in a corresponding way and being found as a multidimensional presence interspersed in songs, is perceived as a substantial or archetypal principle, circulating in the dynamics between imaginary and imagination. Conclusively, it was sought to demonstrate in the four selected songs a potentially sparkling encounter, with varying intensity, throughout the Brazilian popular music phenomenon: an experience of communion with the resonance of being.